Assessing the Hedge and Safe Haven Properties of Gold in Main BIST Sectors via ADCC-GARCH Model: COVID-19 Effects - Serttaş, Fatma Özgü (Current Studies in Social Sciences VI, 2023)
In this study, gold’s safe haven and hedge properties for Borsa Istanbul at the sector level during the COVID-19 pandemic is investigated through utilizing the ADCC-GARCH method. Sectors of BIST: technology (XUTEK), industry (XUSIN), financials (XUMAL), services (XUHIZ) and transportation (XULAS) are considered. Empirical results show that gold has acted as a strong hedge and a weak safe haven asset versus all of the five BIST sector indexes during the COVID-19 pandemic. The results may provide insightful information on more robust risk-hedge and diversification strategies for portfolio investors in Türkiye and abroad.